PELATIHAN DIVERSIFIKASI PRODUK RUMPUT LAUT BAGI WANITA DI TANJUNG BELE, SUMBAWA - Kautsari, Neri; Mardhia, Dwi; Suprianto, Suprianto; Handayani, Fitri; Nurwahidah, Siti (Universitas Mataram, 2024)
Seaweed is one of Tanjung Bele's potential resources, but the macroalgae have not been able to improve the community's economy. This is because seaweed is only sold as dried seaweed. Lack of community knowledge and skills means that seaweed cannot be processed into products with economic value. Therefore, the purpose of this program is to improve the knowledge and skills of the Tanjung Bele community in diversifying seaweed into products with high economic value. This program is carried out in Tanjung Bele Hamlet, Olat Rawa Village, Moyo Hilir District, Sumbawa, West Nusa Tenggara. The target community is the wives of fishermen. The number of people involved in this program is 10 people who are members of the Ai Manis group. The methods used in this activity are counseling, training with active participation methods, evaluation of results using the pretest-posttest method and observation of partner products. This program starts with coordination, continues with counseling and training and ends with evaluation activities. Jelly and seaweed chips are two products made by fishermen's wives. The results of the pretest and posttest showed that most of the target community did not understand the material related to seaweed diversification. This is because most of the community are elementary school graduates and some others have not graduated from elementary school. There are two products produced by partners, namely jelly and seaweed chips.